2002
DOI: 10.1207/s15327027hc1404_5
|View full text |Cite
|
Sign up to set email alerts
|

Bringing the Physician Back In: Communication Predictors of Physicians' Satisfaction With Managed Care

Abstract: Data from a survey of physicians in a west coast city (n = 356) are used to measure physicians' extra-occupational sources of dissatisfaction. Data revealed a significant relationship between physicians' satisfaction and their managed care experience, their communication with managed care organizations, and views of managed care practice. Results suggest that managed care currently plays a large and significant role in predicting physicians' satisfaction. The importance of communication between physicians and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 29 publications
0
7
0
Order By: Relevance
“…Communication variables, in particular, have been measured thanks to the evaluation of problem reporting. [51,52] However, employees' perception of communication and organizational culture seem to be decisively influential on several kind of outcomes, such as job satisfaction, commitment, occupational alienation, perceptions of patient care). [53] More than anything else, the strong influence of practice monitoring on job satisfaction has been demonstrated mostly in organizations where practice is monitored by someone else.…”
Section: Measurement-information System and Motivationmentioning
confidence: 99%
See 1 more Smart Citation
“…Communication variables, in particular, have been measured thanks to the evaluation of problem reporting. [51,52] However, employees' perception of communication and organizational culture seem to be decisively influential on several kind of outcomes, such as job satisfaction, commitment, occupational alienation, perceptions of patient care). [53] More than anything else, the strong influence of practice monitoring on job satisfaction has been demonstrated mostly in organizations where practice is monitored by someone else.…”
Section: Measurement-information System and Motivationmentioning
confidence: 99%
“…[53] More than anything else, the strong influence of practice monitoring on job satisfaction has been demonstrated mostly in organizations where practice is monitored by someone else. [51]…”
Section: Measurement-information System and Motivationmentioning
confidence: 99%
“…In the US, where much of the research has been conducted, various studies highlight what might be regarded as high levels of physician dissatisfaction, especially in primary care settings (McKinlay & Marceau, 2011). The influence of managed care (Stoddard, Hargraves, Reed, & Vratil, 2001) and other factors that reduce "autonomy" is reported as having a negative impact on satisfaction (e. g. Hadley & Mitchell, 2002;Lammers & Duggan, 2002). However, the relationship between satisfaction and perceived autonomy is not straightforward (Tyssen, Palmer, Solberg, Voltmer & Frank, 2013).…”
Section: Learning From the Literaturementioning
confidence: 99%
“…The strength of the patient-physician relationship is highly associated with physicians' satisfaction, especially for family physicians. [ 16 ] Time restrictions, coupled with pressures to see larger volumes of patients, strain this relationship, and also present a barrier to the integration of the psychosocial aspects of medical care. [ 16 ] Potential for conflict and confrontation with patients is a cause of extreme anxiety for physicians, and may precipitate avoidance behaviours to curtail patient discontentment or reproach.…”
Section: Introductionmentioning
confidence: 99%
“…Reports have indicated that important sources of physician satisfaction such as clinical autonomy, [ 9 , 30 ] have eroded with the introduction of managed care budgets, bureaucracy and guidelines. [ 5 , 16 ] Sources of satisfaction such as control over one's work protect against work-related stress, and are important determinants of health and wellbeing. [ 10 , 30 ] Tensions arise if explicit reliance on these performance evaluators are used for health care planning and decision making[ 5 , 6 , 29 , 31 ] without considering the practitioner's element of discretion, duty of non-malfeasance, the contextual complexities, uncertainty in medicine, and differing variations and needs of patients.…”
Section: Introductionmentioning
confidence: 99%